Perkembangan E-Commerce di Indonesia: Regulasi dan Tantangannya - Iskandar, Syahla Atsylah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
E-commerce in Indonesia demonstrated rapid growth due due to the internet's growing popularity, the use of digital technology, and changes in consumer behavior. The main factors that accelerated its development included wide market access, distribution efficiency, and service variation. However, this rapid progress also created regulatory challenges, particularly in terms of legal protection, data security, and transaction certainty. The government had introduced several regulations, such as the Electronic Information and Transactions Law, provisions regarding electronic trading systems, and consumer protection rules. Nevertheless, their implementation still faced obstacles, including weak law enforcement, privacy protection issues, and unfair business practices. This article aimed to identificate the development of e-commerce in Indonesia, evaluate the regulations that had been implemented, and identify the main challenges that needed to be addressed to build a fair, secure, and sustainable digital trade environment.